Microwave‐Assisted Nanocatalysed Synthesis of Phenacyl Halides as Future Anti‐Platelet Agents. Issue 32 (26th August 2019) - Jangid, Dinesh K; Dhadda, Surbhi; Goswami, Prakash G.; Guleria, Anjali; Pareek, Kapil; Jangir, Nidhi; Poonam,
Abstract: An efficient, environmentally benign and novel method for the synthesis of phenacyl halides as antiplatelet agents has been reported in the presence of nanocatalyst (TiO2 ) by using N ‐halosuccinimides (NXS, X=Cl, Br) as a source of halogen and tert‐Butyl Hydrogen Peroxide (TBHP) under microwave irradiation. Compound 2a showed best in vitro antiplatelet activity with 540 and 480 sec as clotting time in prothrombin time (PT) and activated partial thromboplastin time( APTT) assay respectively. Rest compounds showed good to moderate activity. Structures of all synthesized compounds were elucidated by IR, NMR and Mass spectrometry. Abstract : A novel protocol for the α‐halogenation (bromination and chlorination) of carbonyl compounds has been developed by using NXS ( N ‐halosuccinimides), TBHP, TiO2 NPs under microwave irradiation. All synthesized compounds were tested for their in vitro antiplatelet activity, and it was found that compound2 a possesses the highest antiplatelet activity (PT and APTT assay). The rest of the compounds showed good to moderate antiplatelet activity.